Effect of Grapevine Canopy Side on Selected Sensory Attributes of Pinotage and Cabernet Sauvignon Wines - Minnaar, P.P.; Jolly, N.P.; Ntushelo, N.S. (South African Journal of Enology and Viticulture, 2020)
Grapevine row direction, canopy exposure and grape maturity can define the sensory attributes of wine. From this perspective, canopy exposure that favours colour intensity, astringency, aroma intensity and balanced acidity could result in improved wine quality. The aim of this study was to examine the effect of canopy exposure on selected sensory attributes of Pinotage and Cabernet Sauvignon wines from Paarl, Durbanville and Darling in South Africa. Pinotage and Cabernet Sauvignon grapes were harvested from both sides of the canopy of vines planted to E-W and N-S directions. Wines were made from the harvested grapes. Grapes and wines underwent physicochemical and sensory analysis. Durbanville Cabernet Sauvignon from the south side had decreased alcohol content. Total acidity, residual sugar (RS) and pH were not different between sides. Wines from the east side had increased colour, aroma, mouthfeel and overall quality. Paarl Cabernet Sauvignon was not different between sides for any physicochemical characteristics, except TA. Wines from the south side had increased colour, aroma, mouthfeel and overall quality. Darling Pinotage was not different between sides for any physicochemical characteristics. Wines from the west side had increased intensity of aroma and acidity, whereas Durbanville Pinotage from the east side had increased alcohol, pH, TA, colour and aroma intensity, as well as overall quality. The results confirm that canopy exposure has an effect on the wine sensory attributes. This investigation illustrates the variation in sensory attribute scores of Pinotage and Cabernet Sauvignon wines from different canopy sides. Canopy exposure in a vineyard of a specific region, orientated to an E-W or N-S direction, which favours colour intensity, aroma intensity and/or mouthfeel, could result in improved wine quality. Future investigations should focus on samples collected over at least three consecutive vintages, as well as the monitoring of temperature and photosynthetic active radiation.